2017
DOI: 10.1073/pnas.1524845114
|View full text |Cite
|
Sign up to set email alerts
|

SP and IL-33 together markedly enhance TNF synthesis and secretion from human mast cells mediated by the interaction of their receptors

Abstract: The peptide substance P (SP) and the cytokine tumor necrosis factor (TNF) have been implicated in inflammatory processes. Mast cells are recognized as important in inflammatory responses. Here, we report that IL-33 (30 ng/mL), a member of the IL-1 family of cytokines, administered in combination with SP (1 μM), markedly increase (by 1,000-fold) TNF gene expression in cultured human LAD2 and primary mast cells derived from umbilical cord blood. SP (0.01-1 μM) and IL-33 (1-100 ng/mL) in combination also greatly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
107
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 124 publications
(125 citation statements)
references
References 67 publications
4
107
0
2
Order By: Relevance
“…IL‐33 per se does not induce degranulation, but enhances production of CXCL8/IL‐8 and IL‐13 from anti‐IgE‐stimulated human mast cells . IL‐33 enhances substance P‐induced TNF‐α and Vascular Endothelial Growth Factor (VEGF) release from human mast cells . IL‐33 also enhances CXCL8/IL‐8, histamine, and IL‐10 release from immune complex‐triggered human mast cells .…”
Section: Activating Receptors On Human Mast Cells and Basophilsmentioning
confidence: 99%
“…IL‐33 per se does not induce degranulation, but enhances production of CXCL8/IL‐8 and IL‐13 from anti‐IgE‐stimulated human mast cells . IL‐33 enhances substance P‐induced TNF‐α and Vascular Endothelial Growth Factor (VEGF) release from human mast cells . IL‐33 also enhances CXCL8/IL‐8, histamine, and IL‐10 release from immune complex‐triggered human mast cells .…”
Section: Activating Receptors On Human Mast Cells and Basophilsmentioning
confidence: 99%
“…In addition, in the presence of SCF, IL‐33 can also induce TNF production in MCs via a MK2/3‐, ERK1/2‐, and PI3K‐dependent pathway . Recently, Taracanova et al have shown that IL‐33 and SP together amplify TNF secretion from MCs, which is mediated by the interaction of NK‐1R and ST2 receptors . In addition, IL‐33 and FcɛRI act synergistically in the production of TNFα by MCs .…”
Section: Alarmin Receptorsmentioning
confidence: 99%
“…Human skin mast cells express the G‐protein coupled receptor (GPCR) mas‐related gene X2 (MrgX2) that allows them to be activated for degranulation by polybasic substances, such as compound 48/80 and poly‐L‐lysine . Mast cells also express neuropeptide receptors, such as neurokinin 1 and 2 receptors (NK1R and NK2R), calcitonin gene‐related peptide receptor (CGRPR), and the neurotrophin receptors, tropomyosin‐related kinase A (TrkA), TrkB, and TrkC . Neuropeptides such as substance P, vasoactive intestinal peptide (VIP), and somatostatin, but not eledoisin, physalaemin, neurokinin A, neurokinin B, calcitonin gene‐related peptide (CGRP) stimulate both mast cell degranulation and cytokine production .…”
Section: Introductionmentioning
confidence: 99%